Implementation of Da'wah and Rhetoric in Preaching - Mohamad Rifqi (Konsultan Jurnal Ilmiah Indonesia, 2024)
This research aims to determine the implementation of Da'wah and rhetoric in preaching, the method in this research is qualitative, and uses a literature study approach. The results of this research are that in inviting other people to do good and stay away from evil, methods and skills in communicating with people are needed, not only that, we are also required to have a plan in our da'wah actions, after we have established a close relationship with the object of our da'wah then then we have to carry out the plans that we have thought through carefully into action. And of course, in preaching we also have to be consistent and istiqomah so that we and the people we preach are always on the path of Allah SWT until the end of our lives.